The presence of a previous lower limb injury does not affect step asymmetry in elite basketball players: A prospective, longitudinal observational study - Guerra-Armas, J.; Oliva-Hazanas, A.; Hazanas-Ruiz, S.; Torrontegui-Duarte, M.; Cervero-Simonet, M.; Morales-Asencio, J. M.; Pineda-Galan, C.; Flores-Cortes, M.; Luque-Suarez, A. (International Journal of Performance Analysis in Sport, 2023)
This study investigates whether the presence of a previous lower limb injury influences "Lower limb asymmetry" (LLA) in elite basketball players. A prospective, longitudinal observational study was carried out with 13 players grouped based on lower limb injury history in the 3 months prior to the study (Injury = 7, non-injured = 6). A total of 68 measurements per player were collected over 3 months, using the "Inertial Measurement Unit (IMU)" device. The mean difference in, (i) % of step balance; (ii) the average of the number of impacts performed per minute during training and (iii) the player`s load was assessed. This intensive evaluation is in line with the assessment methodology proposed in the field of sports injury. Our results show no significant differences (p = 0.377) in the asymmetry of the step balance between players with/without a history of injury. However, there were differences when the player`s position was considered (p = 0.046). These findings confirm that the presence of a previous lower limb injury does not influence the asymmetry in lower limb step balance in male basketball players. For clinicians, the variables studied offer an indirect measurement of any capacity and/or deficit in the absorption of lower limb loads after an injury.